2010
DOI: 10.2528/pier09122209
|View full text |Cite
|
Sign up to set email alerts
|

An Unbiased Dual-Mode Mixing Antenna for Wireless Transponders

Abstract: Abstract-A zero-bias dual-mode mixing antenna for wireless transponders is proposed in this paper.Designed over an Enhancement-mode Pseudomorphic HEMT (E-PHEMT), the mixer takes advantage of the device nonlinear characteristics around cold operation. Simple closed form expressions, obtained from time-varying circuit analysis, predict good conversion efficiency in two different operating modes without requiring DC bias. For validation, a lab prototype has been implemented and tested, to be finally integrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…RFID (Radio Frequency Identification) is considered an emerging leading technology in future telecommunications [1,2], automatic identification and data capture (AIDC) industries [3]. The RFID market has grown in a two-dimensional trend one side constitutes standalone RFID systems which are commonly found at present [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…RFID (Radio Frequency Identification) is considered an emerging leading technology in future telecommunications [1,2], automatic identification and data capture (AIDC) industries [3]. The RFID market has grown in a two-dimensional trend one side constitutes standalone RFID systems which are commonly found at present [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…As in any amplifier [8][9][10], mixer [11][12][13][14][15][16][17], or active antenna with mixing capabilities [18], noise behavior [11,12] and IF signal distortion [13,18] are key factors that must be rigorously analyzed and minimized. In this work, it will be shown that the figures of merit which are traditionally used to analyze the linearity of conventional mixers cannot be directly applied to an autonomous circuit like the HSOM, because of the influence of the input RF signal power on the parameters of the self-oscillating signal.…”
Section: Introductionmentioning
confidence: 99%
“…Its input impedance also determines the operation regime, since it needs to be modified in order to satisfy the condition imposed by (2). Therefore, it is necessary to have precise control over it at frequencies f o , f r , N × f o and M × f r .…”
Section: Multi-harmonic Load Implementationmentioning
confidence: 99%
“…Therefore, it is a power efficient, very compact and low cost circuit, which can be easily integrated with radiating elements, as a part of low cost active antennas [2][3][4]. However, the main drawback of RSO circuits is that they present very reduced synchronization bandwidth when the synchronization order is high, M, N > 2.…”
Section: Introductionmentioning
confidence: 99%